Detection of 2,4,6-Trinitrotoluene Using a Miniaturized, Disposable Electrochemical Sensor with an Ionic Liquid Gel-Polymer Electrolyte Film - Yu, H.; Lee, J.; Lewis, Simon; Silvester, Debbie (American Chemical Society, 2017)
A new electrochemical method to detect and quantify the explosive compound 2,4,6-trinitrotoluene (TNT) in aqueous solutions is demonstrated. A disposable thin-film electrode modified with a droplet of a gel-polymer electrolyte (GPE) was immersed directly into samples of TNT at concentrations of 1-10 µg/mL. The GPE contained the hydrophobic room-temperature ionic liquid (RTIL) trihexyltetradecylphosphonium bis(trifluoromethylsulfonyl)imide ([P14,6,6,6][NTf2]) and the polymer poly(hexyl methacrylate). The RTIL acted to preconcentrate TNT into the GPE and provided ionic conductivity. The polymer provided both (i) sufficient viscosity to ensure mechanical stability of the GPE and (ii) strong hydrophobicity to minimize leaching of the RTIL. Square wave voltammetry was performed on the first reduction peak of TNT-preconcentrated samples (15 min soaking with mechanical stirring), with linear plots of peak current vs cumulative concentration of TNT, giving an averaged limit of detection of 0.37 µg/mL (aqueous phase concentration). Additionally, the voltammetry of the first reduction peak of TNT in [P14,6,6,6][NTf2] was unaffected by the presence of oxygen-in contrast to that observed in an imidazolium-based RTIL-providing excellent selectivity over oxygen in real environments. The sensor device was able to quickly and easily quantify TNT concentrations at typical ground water contamination levels. The low-cost and portability of the sensor device, along with the minimal amounts of GPE materials required, make this a viable platform for the onsite monitoring of explosives, which is currently a significant operational challenge.